Blended Assesment Dalam Pembelajaran Fikih Untuk Menilai Aspek Kognitif Peserta Didik - Tatag Satria Praja; Muslih; Siti Fauziyah (Mudir : Jurnal Manajemen Pendidikan, 2019)
Assessment has a very vital role in learning process. In Jurisprudence learning many teachers focus on written cognitive assessment, where results become a matter of pride, teachers often forget to assess student understanding, practice and creativity, even though 21st century assessment demands the latest knowledge and abilities. This article uses a blended assessment (tahriri, syafahi, and capstone project) as an alternative solution to cognitive assessment, the assessment of fiqh learning will be comprehensive and make the product of learning. This article includes a literature study with a qualitative-descriptive approach. The result is blended assessment is a combination of two or more types of assessments, to determine students' abilities and improve the quality of learning. Blended assessment in fiqh learning cognitive aspects, has a level, that tahriri test consisting of C1 and C2, functioning to assess memory skills and comprehension, syafahi test consists of C3 and C4, functioning to assess applicative and analytical abilities, and capstone projects consisting of C5 and C6, to assess the evaluation skills and creations of students. The method of evaluation by combining results of tahriri, syafahi, and capstone projects, the percentage is 30 percent tahriri, 30 percent syafahi, and 40 percent capstone project. Three tests are combined into one with the percentage and value of each test result.